The Effects of Intravermis Cerebellar Microinjections of Dopaminergic Agents in Motor Learning and Aversive Memory Acquisition in Mice - Guilherme, Evelyn M.; Gianlorenço, Anna Carolyna L. (Frontiers in Behavioral Neuroscience, 2021)
The cerebellum receives dopaminergic innervation and expresses the five types of described dopaminergic receptors. The cerebellar function involves both motor movement and cognition, but the role of cerebellar dopaminergic system on these processes remain unclear. The present study explores the behavioral responses to intracerebellar microinjection of dopaminergic agents in motor and emotional memory. For this, naïve Swiss mice had their cerebellar vermis implanted with a guide canula, received a intravermis microinjection of Dopamine, D1-like antagonist SCH-23390 or D2-like antagonist Eticlopride, and underwent a behavioral analysis of motor learning (by a Rotarod and balance beam learning protocol) or aversive memory acquisition (by the inhibitory avoidance task). The mixed-effects analysis was used to evaluate groups performance, followed by Tukey’s post hoc when appropriated. In this study, Dopamine, SCH-23390 and Eticlopride at the doses used did not affected motor control and motor learning. In addition, the administration of Dopamine and SCH-233390 had no effects on emotional memory acquisition, but the animals that received the highest dose of Eticlopride had an improvement in aversive memory acquisition, shown by a suppression of its innate preference for the dark compartment of the inhibitory avoidance apparatus following an exposure to a foot shock. We propose that cerebellar dopaminergic D2 receptors seem to participate on the modulation of aversive memory processes, without influencing motor performance at the doses used in this study.